Law Making Treaties: The Implication of International Law towards Indonesia’s Legislations - Rudi Natamiharja; Rudy Rudy; Chaidir Ali (Jambe Law Journal, 2020)
In relation to promoting global issues in international forums, several sources of international law are formed. These formed laws are in the figure of law-making treaties, which are closely related to international regimes that influence the behavior of international actors. However, in developing countries, such as Indonesia, International law is considered the outermost layer of the legal order under national law, colonial law, religious law, and customary law. Thus, it is a challenge for international laws to be enforced in a broad society. Therefore to make international law hold an implementative power, the laws need to be adopted in the national law. This article aims to examine the implication of international laws, especially in international treaties towards Indonesia legislation. It is carried out by mapping a series of international treaties ratified and enacted through national laws in Indonesia. The results of this study demonstrates that until 2019 the Indonesian Government has bound itself in 302 agreements. From the 302 treaties, only 61 international treaties were Law-Making Treaty, and only UNCLOS 1982 has implicated by the Indonesian Government through Law No. 32 of 2014 concerning Maritime Law.